Simplifying
2x3 + 2 = 0
Reorder the terms:
2 + 2x3 = 0
Solving
2 + 2x3 = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 2x3 = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 2x3 = 0 + -2
2x3 = 0 + -2
Combine like terms: 0 + -2 = -2
2x3 = -2
Divide each side by '2'.
x3 = -1
Simplifying
x3 = -1
Reorder the terms:
1 + x3 = -1 + 1
Combine like terms: -1 + 1 = 0
1 + x3 = 0
The solution to this equation could not be determined.